THE RECEPTION OF THE PHILOSOPHICAL TRADITION AS A WAY OF FORMING AMERICAN PERSONALISM: THE POST-SECULAR VIEW - V. O. Patsan (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2016)
The aim of the article is to define the way of expounding the authenticity of the experience of self-cognition opened by the personalist philosophy of the USA on the horizon of receiving the philosophical tradition established by B. P. Bowne to lay the epistemological foundations for overcoming the impersonalist modes of thought in the philosophical-humanitarian space of North America. At the emergent stage of the historical-philosophical process defined as its post-secular period the topicality of studying American personalism in the indicated aspect of its genesis is predetermined by developing the personalistic inspiration of post-non-classical philosophy into renewing the interaction of philosophical and theological discourses initial for the personalist thought and intended to reunite rationality with its spiritual sources in the course of reflecting the personal mode of being realized on the ground of theism. The further reflection of the meta-ontology of the personhood uncovered by the Scripture and expounded by patristic trinitology presupposes the retrospection of the trajectory of moving towards the Supernatural Revelation paved in the late nineteenth and the first half of twentieth centuries by the attempts of personalizing the ontology, in particular by the “personalized” ontological constructions made in the USA. The methodology of the research is based upon realizing the meta-ontological character of the problem of the personality revealed in the midst of the twentieth century by the prominent Orthodox theologian and philosopher-personalist V. N. Lossky. Taking into consideration the Biblical background of American personalism and its genetic connections with the denominations of Protestantism developed on the North American continent and the branching Protestant theology, the author focuses on both proper philosophical and theological reference points of this personalistic current of philosophizing in the historical-philosophical reconstruction of its genesis oriented towards the meta-ontological dimension of the personality. The scientific novelty of the study consists in initiating the reflection of the way of defining the inner experience of the self as the all-sufficient criterion of cognition which was paved by the personalist thought of the USA in the course of revising the classical rationalist models of the subjectivity and broke the ground for constructing “the personal world” in the space of rational consciousness formed in North America. On the base of analyzing Bowne's revision of Kant's transcendental idealism aimed at the explication of the immediacy of self-experience the author reveals that such argumentation for its cognitive primacy transforms into affirming the mediation of the inner appeal of the human personality to living God by the outer interpersonal experience of rational cognition. The revealed regression to the rationally mediated relationship of the created person with Creator is connected with the restriction of the research for “personal beginning of all speculation” which resulted in the personal metaphysics of B. P. Bowne by the rationalistic tools of the personal self-reflection. The study proves that it was predetermined by the philosopher's confessional belonging to the Methodist Church detached from patristic Trinitology and Christology forming the arsenal of trinitarian meta-logic intended to expound the personhood as the ultimate principle of being. Conclusions define the resource of Bowne's idea of the “personal interpretation of experience” which inspired the subsequent “personalized” ontological constructions in the personalistic domain established on the North American continent. They form the dialogic space of the personalist philosophy of the USA predetermining the accumulation of its potential in the interaction with other philosophical currents. Manifesting itself as the personalistic inspiration of the emerging trends of thought this tendency predicts the focus of the further historical-philosophical research of American personalism.